2022
DOI: 10.1007/s11368-022-03155-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic matter degradation in cohesive sediment: linking sediment rheology to spatio-temporal patterns of organic matter degradability

Abstract: Purpose Sediment organic matter (SOM) influences settling and thus the rheological behavior of suspended particles by enhancing flocculation or reducing surface charges by forming organo-mineral complexes that facilitate particle–particle interactions in consolidating sediments. It was, therefore, assumed that the microbial degradation of SOM and its spatio-temporal variability would affect sediment rheological properties and enhance port maintenance dredging and navigability of ports and waterwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They presented three studies conducted for the Hamburg and Rotterdam Port Authorities. Zander et al ( 2022 ) presented the effects of microbial organic matter degradation on sediment rheological properties. After exposing sediments collected from Port of Hamburg, Germany, for 250 days in glass bottles to aerobic and anaerobic conditions in a laboratory environment, they found that degradation of organic matter significantly reduces the sediment strength, especially under anaerobic conditions.…”
Section: Sediment Assessment and Management – Concepts And Policiesmentioning
confidence: 99%
“…They presented three studies conducted for the Hamburg and Rotterdam Port Authorities. Zander et al ( 2022 ) presented the effects of microbial organic matter degradation on sediment rheological properties. After exposing sediments collected from Port of Hamburg, Germany, for 250 days in glass bottles to aerobic and anaerobic conditions in a laboratory environment, they found that degradation of organic matter significantly reduces the sediment strength, especially under anaerobic conditions.…”
Section: Sediment Assessment and Management – Concepts And Policiesmentioning
confidence: 99%
“…Focusing on the microscale, the soil organic carbon (SOC) content is one of the chemical-physical properties that can play a role in mudflow triggering, evolution, and arrest [13]. SOC originates from plants, animals, and microorganisms and their exudates.…”
Section: Introductionmentioning
confidence: 99%
“…Sills and Gonzalez (2001) and Jommi et al (2019) have demonstrated strong reduction in shear stresses by gas originating from organic matter decay. The (anaerobic) decay of organic matter leads to the generation of methane gas, delays sediment consolidation, reduces sediment density, viscosity and shear strength (Shakeel et al, 2022;Zander et al, 2022), impacting flow properties and therefore the navigable depth. Given the effects organic matter can exert on the physical behaviour of fine-grained sediment (mud), it is of interest to assess its lability, or, inversely, its stability or recalcitrance towards microbial degradation.…”
Section: Introductionmentioning
confidence: 99%